URGENSI LINGKUNGAN BELAJAR YANG KONDUSIF DALAM MENDORONG SISWA BELAJAR AKTIF - ARIANTI, ARIANTI (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2017)
This journal discusses the urgency of a conducive learning environment in encouraging students to learn actively. A conducive school learning environment is closely related to the quality of student learning. It is realized that a conducive class can prevent students from boredom, boredom and psychological fatigue, while another conducive class conducts motivation and endurance in learning. In an active learning environment, students are not burdened individually in solving problems encountered in learning, but they can ask each other and discuss so that the burden of learning for them did not happen. With this active learning strategy is expected to grow and develop all the potential that they have so that in the end can optimize their learning results. Therefore, in the learning process of teachers play a role as mentors. Teachers should try to enliven and motivate students to create a conducive interaction process in the learning process in the classroom. In an active learning process it occurs a dialogue that interactions between students with students, students with teachers or students with other learning resources.